Hand-off the foreign policy George W. Bush passed to Barack Obama - Hadley, Stephen J. 1947-; Feaver, Peter 1961-; Inboden, William 1972-; O'Sullivan, Meghan L. 1969- (Brookings Institution Press, 2023)
"This book details the Bush administration's national security and foreign policy as described at the time in then-classified transition memoranda prepared by the National Security Council experts who advised President Bush"--
Keywords: Geschichte 2001-2016; Außenpolitik; USA; United States / Foreign relations / 21st century; Bush, George W. / (George Walker) / 1946-; United States / Foreign relations / 21st century / Sources; National security / United States / History / 21st century / Sources; United States / Politics and government / 2001-2009; Presidents / United States / Transition periods; Diplomatic relations; National security; Politics and government; Presidents / Transition periods; United States; 2000-2099; History; Sources